In vitro exposure of DE‐71, a penta‐PBDE mixture, on immune endpoints in bottlenose dolphins (Tursiops truncatus) and B6C3F1 mice. Issue 2 (7th April 2014) - Wirth, Jena R.; Peden‐Adams, Margie M.; White, Natasha D.; Bossart, Gregory D.; Fair, Patricia A.
ABSTRACT Polybrominated diphenyl ethers (PBDEs) are an emerging contaminant of concern with low level exposures demonstrating toxicity in laboratory animals and wildlife, although immunotoxicity studies have been limited. Bottlenose dolphin peripheral blood leukocytes (PBLs) and mouse splenocytes were exposed to environmentally relevant DE‐71 (a penta‐PBDE mixture) concentrations (0–50 µg ml−1) in vitro. Natural killer (NK) cell activity and lymphocyte (B and T cell) proliferation were evaluated using the parallelogram approach for risk assessment. This study aimed to substantiate results from field studies with dolphins, assess the sensitivities between the mouse model and dolphins, and to evaluate risk using the parallelogram approach. In mouse cells, NK cell activity increased at in vitro doses 0.05, 0.5 and 25 µg DE‐71 ml−1, whereas proliferation was not modulated. In dolphin cells, NK cell activity and lymphocyte proliferation was not altered after in vitro exposure. In vitro exposure of dolphin PBLs to DE‐71 showed similar results to correlative field studies; NK cell activity in mice was more sensitive to in vitro exposure than dolphins, and the parallelogram approach showed correlation with all three endpoints to predict risk in bottlenose dolphins. Copyright © 2014 John Wiley & Sons, Ltd.